Aplicação da tecnologia supercrítica no tratamento de resíduos plásticos presentes em amostras de água - Viana , Júlio Cezar Vieira (2023)
Phthalic acid esters (PAEs) and bisphenol A (BPA) are plastic waste classified as emerging organic contaminants that can harm biota and human health. These residues arise as a result of the fragmentation of plastics into their monomers or the leaching of compounds used as plasticizers, such as BPA and DEP. In addition to contaminants of emerging concern, these compounds are also classified as endocrine disruptors (EDCs), interacting with estrogen receptors and causing harm to human health and the environment. Even with the availability of physical and chemical wastewater treatment methods, classical treatment methods for these compounds have proven not to be efficient in removing these refractory compounds. Therefore, the objective of this work was to use supercritical water oxidation (OASC) technology to investigate the degradation of BPA and DEP plastic waste in aqueous samples. The variables flow rate, temperature, concentration of oxidizing agent (H2O2) and homogeneous and heterogeneous catalyst, such as Cu(NO3)2 and metallic copper wire, respectively were used as parameters for the tests. Metallic copper was also used in the form of a wire together with H2O2. After treatment using OASC Total organic carbon (TOC) removal efficiencies were found to increase linearly with increasing temperature in the range of 400°C to 700°C for all tests with BPA and DEP. For all tests carried out, the best efficiency in removing total organic carbon (TOC) for BPA was achieved at a temperature of 700°C, oxidant concentration of 60 mM and flow rate of 10 mL.min-1 , reaching 91% of removal. For DEP, the best removal efficiency was achieved at a temperature of 700°C, oxidant concentration of 23 mM and flow rate of 10 mL.min-1, achieving 85% removal. Gas chromatography analysis was carried out for the gaseous components and revealed the presence of hydrogen, carbon dioxide, ethane, ethylene, methane and carbon monoxide gases. The analysis of the liquid fraction for BPA samples in the best treatment condition was carried out using liquid chromatography coupled to mass spectrometry and revealed the presence of the intermediate 2-phenyl2-propanol as the main degradation product. The liquid fraction for DEP samples in the best treatment condition was performed by gas chromatography coupled to mass spectrometry and revealed the presence of aliphatic chain hydrocarbons, such as decosane, triacontane, tetracosane and eicosane as the main degradation products. Therefore, the use of supercritical technology proved to be an efficient method for treating aqueous samples containing BPA and DEP.